Color Doppler imaging characteristics of RPE neoplasms: A study of 17 cases - Zhou, Nan; Yang, Wenli; Wei, Wenbin (Frontiers in Ophthalmology, 2022)
Purpose To report the color Doppler imaging (CDI) features of 17 patients with retinal pigment epithelium (RPE) neoplasms. Design Retrospective, observational case series. Participants Seventeen patients with RPE adenoma/adenocarcinoma. Methods Contrast-enhanced color Doppler ultrasonography (CDU) was performed in 16 patients with RPE adenoma and in one patient with adenocarcinoma. Result All 17 RPE neoplasms showed well-defined margins. An oval mass was observed in 11 tumors, a lenticular-shaped mass in four tumors, and a flat mass in two tumors. On CDI, RPE lesions showed homogeneous reflectivity of moderate intensity with no choroidal excavation. After the contrast-enhanced administration of sulfur hexafluoride, mild enhancement was identified in six tumors and moderate enhancement in 11 tumors. In all 17 RPE neoplasms, contrast-enhanced CDU time–intensity curves (TICs) exhibited fast fill-in and slow washout-shaped curves with the dominant vessel within RPE lesions. A “black-linear” sign (defined as a low signal intensity-linear zone located between the tumor and enhanced choroid on CDI) was noted in all 17 patients with RPE neoplasms. Conclusions This preliminary study noted a “black-linear” sign on CDI of RPE lesions for the first time. The novel sign may be a diagnostic characteristic of RPE neoplasms and may help to distinguish this rare entity from uveal melanomas (UMs).